Demographic factors, food security, health related quality of life and body weight status of adolescents in rural area in Mentakab, Pahang Malaysia - Susanti Alie; Sulaiman, Norhasmah; Mohd Nor, Fadilah; Mesbah, Siti Farhana (Nutrition Society of Malaysia, 2019)
Introduction: Adequate, nutritive and safe foods are crucial for growth and healthy living. Adolescents are vulnerable to food insecurity. This study was aimed at determining the demographic factors, food security status, health-related quality of life (HRQOL) and body weight status of adolescents in Mentakab, Pahang, Malaysia. Methods: This study involved 160 households that comprised pairs of mothers and children aged 13-17 years. Face-to-face interviews were conducted with the mothers to assess their demographic and food security status (Radimer/Cornell Hunger and Food Insecurity Instrument). Meanwhile, the children answered a self-administered HRQOL questionnaire (Pediatric Quality of Life Inventory, PedsQL). Body weight and height were measured to obtain the body mass index (BMI). Results: About 48.8% of the adolescents were from households with food insecurity. The number of school-going siblings, occupation status of mother, occupation status of father, household income and house ownership status were predictors of food security status (p<0.05). After controlling for covariates, the HRQOL score and BMI were higher in adolescents from food-secure households than adolescents from foodinsecure households (p<0.01). Conclusion: The prevalence of food insecurity was high and multifactorial. Food insecurity was further associated with HRQOL and BMI. Food assistance programmes are recommended to directly alleviate food insecurity. Concurrently, monetary and educational aids are advocated to reduce the economic burden, especially in low-income households.